PENGARUH KEDISIPLINAN KERJA, EFIKASI DIRI DAN KOMPENSASI TERHADAP KOMITMEN PROFESIONAL GURU PAUD DI KECAMATAN GUNUNGSINDUR - Rukka, Usmawaty Rukka; Anwar, Saiful; Zubaidah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effects of work discipline, self-efficacy, and compensation on the professional commitment of early childhood education (ECE) teachers in Gunungsindur District. The study employed a quantitative approach using a survey method. The research population consisted of ECE teachers affiliated with HIMPAUDI and PKG in Gunungsindur District, with a total sample of 111 respondents. Data were collected using a questionnaire and analyzed through correlation analysis, simple regression, multiple regression, and partial correlation using SPSS version 23. The results indicate that work discipline has a positive and significant effect on teachers’ professional commitment with a correlation coefficient of r = 0.920 and a contribution of 92.0%. Compensation also shows a positive and significant effect with r = 0.660 (contribution 66.0%), while self-efficacy has a positive and significant effect with r = 0.840 (contribution 84.0%). Simultaneously, work discipline, compensation, and self-efficacy have a positive and significant effect on professional commitment with a combined contribution of 16.8%. These findings suggest that strengthening work discipline, enhancing self-efficacy, and providing fair compensation are essential to improving the professional commitment of ECE teachers.